Fit αβ T-cell receptor suppresses leukemogenesis of Pten-deficient thymocytes - Gon, Stéphanie; Loosveld, Marie; Crouzet, Thomas; Potier, Delphine; Bonnet, Mélanie; Morin, Stéphanie O.; Michel, Gérard; Vey, Norbert; Nunès, Jacques A.; Malissen, Bernard; Roncagalli, Romain; Nadel, Bertrand; et al. (Haematologica (Roma), 2018)
Signaling through the αβT cell receptor (TCR) is a crucial determinant of T-cell fate and can induce two opposite outcomes during thymocyte development: cell death or survival and differentiation. To date, the role played by T-cell receptor in the oncogenic transformation of developing T cells remains unclear. Here we show that human primary T-cell acute lymphoblastic leukemias expressing an αβT cell receptor are frequently deficient for phosphatase and tensin homolog protein (PTEN), and fail to respond strongly to T-cell receptor activation. Using Pten-deficient T-cell acute lymphoblastic leukemia mouse models, we confirm that T-cell receptor signaling is involved in leukemogenesis. We show that abrogation of T-cell receptor expression accelerated tumor onset, while enforced expression of a fit transgenic T-cell receptor led to the development of T-cell receptor-negative lymphoma and delayed tumorigenesis. We further demonstrate that pre-tumoral Pten-deficient thymocytes harboring fit T-cell receptors undergo early clonal deletion, thus preventing their malignant transformation, while cells with unfit T-cell receptors that should normally be deleted during positive selection, pass selection and develop T-cell acute lymphoblastic leukemias. Altogether, our data show that fit T-cell receptor signaling suppresses tumor development mediated by Pten loss-of-function and point towards a role of Pten in positive selection.